Representation of Cultural Hybridity in The Asian American Comedy Film 'Joy Ride' 2023 - Syaniah, Fikriyah; Lestari, Indah (ITScience (Information Technology and Science), 2025)
This study examines cultural hybridity in the film Joy Ride (2023), which blends Western and Asian cultural elements. Understanding cultural hybridity is crucial in the era of globalisation to foster mutual respect and avoid subjective negative perceptions of foreign cultures. This research aims to analyse the forms, processes, and purposes of cultural hybridity depicted in the film. A qualitative descriptive method was employed with a constructive paradigm, applying Ferdinand de Saussure's structural semiotics. The findings were further analysed using Homi K. Bhabha's concept of cultural hybridity, which includes hybridity, mimicry, and ambivalence. The study identified 11 instances of hybrid culture reflected in the characters' daily lives. Mimicry is observed in four key aspects, such as Lolo’s gesture of raising her middle finger in a photo, symbolising an adaptation of Western norms. Additionally, the characters adopt K-pop-inspired fashion to gain social acceptance. Audrey’s professional success as a lawyer and Lolo’s reputation as